Touching Philosophy, Sounding Religion, Placing Education. - Schroeder, Steven (BRILL, 2002)
This book redefines religious studies as a field in which a plurality of disciplines interact. A social science when understood as a body of knowledge, religion is also marked by discovery, appreciation, orientation, and application-an interplay of the arts and sciences. Teaching religious studies involves the question of the occupation of territories and disentangling occupation from violence.
Description based upon print version of record.
Keywords: Religion -- Philosophy.; Religion -- Study and teaching.; Religion -- Philosophie.; Religion -- Étude et enseignement.